2021
DOI: 10.1177/10963480211031399
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchal Formation of Trust on Peer-to-Peer Lodging Platforms

Abstract: Based on the concept of trust from a hierarchical approach and with the support of processing fluency theory, the current study investigates customer trust, and its relationships with flow experience, satisfaction, and repatronage intention on peer-to-peer (P2P) lodging platforms. Customer flow experience on the Airbnb platform is verified to be an antecedent of economy-based trust. The hierarchical organization of trust is also proved applicable in the context of sharing economy websites (economy-based trust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 95 publications
0
13
0
Order By: Relevance
“…However, trust in sharing accommodation is multifaceted and complex. It should be differentiated from that in the traditional context because this marketplace has more uncertainties and risks, such as personal information leakage, as well as private and financial risks (Luo et al , 2022). The first reason is the diversity of participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, trust in sharing accommodation is multifaceted and complex. It should be differentiated from that in the traditional context because this marketplace has more uncertainties and risks, such as personal information leakage, as well as private and financial risks (Luo et al , 2022). The first reason is the diversity of participants.…”
Section: Resultsmentioning
confidence: 99%
“…The transaction subjects of sharing accommodation include consumers, hosts and platforms (such as Airbnb), but traditional e-commerce transactions only include consumers and corporate websites (Xie and Mao, 2017). Second, consumers and hosts interact online and offline (Luo et al , 2022). Third, hotels can provide consumers with consistent and standardized service, unlike individual providers, who lack a strong reputation (Prayag and Ozanne, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Airbnb is one of the growing companies in the hospitality industry that relies on sharing economy to conduct business, and to connect hosts to travelers [6]. As one of the leading companies in this industry, Airbnb operates on an innovative marketplace platform as an intermediary to serve the needs of travelers.…”
Section: Literature Review 21 Airbnb Corporate Model and Business Str...mentioning
confidence: 99%
“…As the brand mainly communicates with its users virtually, trust might greatly influence customers and affect profitability [6]. An article about Airbnb indicated that trust has direct and indirect effects on customer satisfaction and repurchase intention [7,8].…”
Section: Literature Review 21 Airbnb Corporate Model and Business Str...mentioning
confidence: 99%
See 1 more Smart Citation